Factors Influencing Academic Motivation of Ethnic Minority Students: A Review. (June 2018) - Isik, Ulviye; Tahir, Omaima El; Meeter, Martijn; Heymans, Martijn W.; Jansma, Elise P.; Croiset, Gerda; Kusurkar, Rashmi A.
The aim of this study to create a comprehensive overview of factors that may influence motivation of ethnic minority students from their own perspective. A systematic review was conducted in PubMed, ERIC, and PsycINFO to find studies in which the motivation of ethnic minority students was studied. The articles reviewed were qualitatively synthesized by means of meta-ethnography, and were subjected to a quantitative meta-analysis where appropriate. Forty-five articles were included. Several factors were found to have either a positive or a negative influence on academic motivation, which can be classified into individual, family-related, school-related, and social factors. These factors should be taken into account when developing interventions aimed at enhancing motivation, which is expected to improve. However, evidence for the influence of most identified factors is weak, given that almost every factor was investigated in a single study only. Based on the outcomes of the current overview an integrative model, that provides a structure of the identified factors in relation to motivation which can be used for interventions, cannot be generated; thus, further research is needed.